Joint association of sleep patterns and oxidative balance score with all-cause and cardiovascular mortality among the general population - Chen, Chen; Wu, Hanzhang; Jin, Hongyu; Jiang, Zhiping; Wang, Wei; Tan, Xiao; Li, Wen-Yang (Frontiers in Nutrition, 2025)
BackgroundThis study investigates the joint effect of sleep patterns and oxidative balance score (OBS) on all-cause and CVD mortality in the general population.MethodsWe examined 21,427 individuals aged 18–85 from NHANES 2005–2014, connecting them to mortality data until December 31, 2019, using interview and physical examination dates. Surveys collected data on sleep duration, self-reported sleep disturbance, and doctor-told sleep disorders, classified into healthy, intermediate, and unhealthy sleep patterns. OBS was calculated based on twenty oxidative stress-related exposures to dietary and lifestyle factors. Cox proportional hazards model was conducted to evaluate the association between sleep patterns or OBS alone and combined with all-cause and CVD mortality.ResultsPoor sleep patterns and pro-oxidant OBS (Q1 & Q2) were identified as risk factors for mortality. Each point increase in OBS was associated with a 3% decrease in both all-cause mortality and CVD mortality. There was an interaction between sleep patterns and OBS (P for interaction = 0.013). Joint analyses revealed that participants with combined unhealthy (intermediate and poor) sleep pattern and pro-oxidant OBS were significantly associated with increased risk of all-cause (HR = 1.45 [1.21–1.74]) and CVD mortality (HR = 1.60 [1.12–2.28]). Furthermore, stratified analysis highlighted that this joint effect was more prominent among individuals without hypertension or diabetes; more notable for all-cause mortality in younger individuals and for CVD mortality in the elderly.ConclusionWe identified a significant interaction between sleep patterns and OBS affecting all-cause mortality. Unhealthy sleep patterns and pro-oxidant OBS were jointly and positively associated with an increased risk of all-cause and CVD mortality. Interventions targeting healthy sleep patterns and antioxidant lifestyles may promote health outcomes.